Interpreting for the military: Creating communities of practice - Lucia Ruiz Rosendo (JoSTrans: The Journal of Specialised Translation)
This article explores the creation of communities of practice in the context of military training and capacity-building missions deployed by Western armed forces in countries in conflict. It reports on a participatory study with Spanish military officers deployed in Afghanistan and civilian interpreters who worked for them. The discussion is framed in new military doctrines that advocate for strengthening local forces of countries in conflict and premised on Lave and Wenger's (1991) social theory of learning. The article argues that, when civilian interpreters start to work for the military, they lack knowledge of military procedure and of interpreting skills. For their part, the military personnel are generally not aware of the non-linguistic elements and culture-specific aspects of communication. Group cohesion is created, allowing for an iterative exchange of information and a constant learning process. Since civilian interpreters have not been trained before being recruited by the armed forces, their role as interpreters is contingent on their role as legitimate peripheral participants in the military sphere. The interpreters' personal background and their language proficiency in Spanish conditioned their degree of participation in the community of practice.